Mycorrhizal population on various cropping systems on sandy soil in dryland area of North Lombok, Indonesia - WAHYU ASTIKO; MUHAMMAD TAUFIK FAUZI; SUKARTONO SUKARTONO (Nusantara Bioscience, 2016)
Abstract. Astiko W, Fauzi MT, Sukartono. 2016. Mycorrhizal population on various cropping systems on sandy soil in dryland area of North Lombok, Indonesia. Nusantara Bioscience 8: 66-70. Inoculation of arbuscular mycorrhizal fungi (AMF) on maize in sandy soil is expected to have positive implications for the improvement of AMF population and nutrient uptake. However, how many increases in the AMF population and nutrient uptake in the second cycle of a certain cropping system commonly cultivated by the farmers after growing their corn crop have not been examined. Since different cropping systems would indicate different increases in the populations of AMF and nutrient uptake. This study aimed to determine the population AMF and nutrient uptake on the second cropping cycle of corn-based cropping systems which utilized indigenous mycorrhizal fungi on sandy soil in dryland area of North Lombok, West Nusa Tenggara, Indonesia. For that purpose, an experiment was conducted at the Akar-Akar Village in Bayan Sub-district of North Lombok, designed according to the Randomized Complete Block Design, with four replications and six treatments of cropping cycles (P0 = corn-soybean as a control, in which the corn plants were not inoculated with AMF; P1 = corn-soybean, P2 = corn-peanut, P3 = corn-upland rice, P4 = corn-sorghum, and P5 = corn-corn, in which the first cycle corn plants were inoculated with AMF). The results indicated that the mycorrhizal populations (spore number and infection percentage) were highest in the second cycle sorghum, achieving 335% and 226% respectively, which were significantly higher than those in the control. Increased uptake of N, P, K and Ca the sorghum plants at 60 DAS of the second cropping cycle reached 200%; 550%; 120% and 490% higher than in the control. The soil used in this experiment is rough-textured (sandy loam), so it is relatively low in water holding capacity and high porosity.